Pour une approche géographique des jeux de plateau - Manouk Borzakian (Cybergeo)
The geography of board games practices, which remains to be written, cannot avoid a preliminary research on the games themselves and their inner logic. Within that framework, "traditional" board games have the interest of being possibly considered as models of social reality and lend themselves to an investigation of a geographical nature. The study of the features of these play spaces – scale, metrics, substance – and of the nature of their relationship is a first step towards a typology of games, based on the representations of space conveyed by them. Such a typology is a crucial step towards the writing of a geography of practices.